Bioactive glyceroglycolipids from marine macroalgae: Isolation, purification, and food preservation potential - Sun, Yingying; Zhang , Yu; Mao , Chenwei; Mu , Yang; Li , Tianle; Jiang , Xiujing; Hu, Yadong; Pan , Mingxuan; Yu , You; Wang, Haonan; Wei, Xin (International Journal of Agricultural and Biological Engineering, 2026)
Macroalgae represent valuable marine resources, being rich in bioactive glyceroglycolipids with antioxidant and anti-inflammatory properties. In this study, the extraction processes for glyceroglycolipids from Palmaria palmata, Chorda filum, and Enteromorpha clathrata were systematically optimized. Using single-factor and response surface methodologies, optimal extraction conditions were established, achieving yields of 69.96 mg/g, 65.14 mg/g, and 85.73 mg/g, respectively. The resultant extracts were subsequently evaluated for their antioxidant and hygroscopic-moisturizing activities. It was observed that the glyceroglycolipid extracts exhibited a significant, concentration-dependent increase in the scavenging of DPPH, hydroxyl, and ABTS radicals, although their overall efficacy remained lower than that of vitamin C. In terms of hygroscopic and moisturizing properties, the extracts performed better than hyaluronic acid but were inferior to glycerol across varying humidity conditions. Further purification employing liquid-liquid extraction, thin-layer chromatography, and silica gel column chromatography enabled the isolation of specific glyceroglycolipid fractions. Additionally, treatment of Channa argus fillets with these glyceroglycolipids resulted in improved physicochemical indices compared to the control group, effectively delaying spoilage. These findings underscore the potential of marine macroalgae-derived glyceroglycolipids in food preservation, providing a solid foundation for further research and application within the food industry. Keywords: macroalgae, glyceroglycolipids, response surface design, anti-oxidant activity, food preservation DOI: 10.25165/j.ijabe.20261901.10113 Citation: Sun Y Y, Zhang Y, Mao C W, Mu Y, Li T L, Jiang X J, et al. Bioactive glyceroglycolipids from marine macroalgae: Isolation, purification, and food preservation potential. Int J Agric & Biol Eng, 2026; 19(1): 270–282.